Research and development capitalization, fair value, and earnings management: A study of French listed companies - Yosr Hrichi; Feten Arfaoui (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- This paper investigates the problem of the multitude of accounting choices allowed by international accounting in the French context. Motivation- The discretionary accounting choices of capitalization of development costs and the use of fair value in the French context of written law impact earning management. Idea- The choice of the French context is explained by the fact that France is a country of written law where accounting choices differ from countries of common law, especially in different requirements in terms of transparency. Data- We adopt two empirical models of earnings management based on linear regressions. Tools- The first is based on discretionary accruals and the second relies on the correlation between total accruals and operational cash flows. Findings- Based on a sample of 100 French companies belonging to the SBF 120 between 2000 and 2020 the linear regressions suggest that the capitalization of development costs increases earnings management by manipulating the amount of the expenses, the period of amortization, and the choice of the depreciation method. However, the choice of fair value decreases earnings management and signals the commitment to accounting transparency by improving the relevance and limiting the possibility of manipulation. Contribution- This study highlights the problem of accounting choices permitted for capitalization decisions regarding development costs and fair value.
Keywords: M41; 650; Earning management; Research and Development; Fair value